2021
DOI: 10.3390/ijms22126497
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear and Muscle Developmental Defects in Smpx-Deficient Zebrafish Embryos

Abstract: The last decade has witnessed the identification of several families affected by hereditary non-syndromic hearing loss (NSHL) caused by mutations in the SMPX gene and the loss of function has been suggested as the underlying mechanism. In the attempt to confirm this hypothesis we generated an Smpx-deficient zebrafish model, pointing out its crucial role in proper inner ear development. Indeed, a marked decrease in the number of kinocilia together with structural alterations of the stereocilia and the kinociliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
(88 reference statements)
2
7
0
Order By: Relevance
“…The Smpx localization in the primary cilium strongly supports the observation that the Smpx-positive cells are the actual mechanosensory HCs responsible for the conversion of mechanical stimuli into electric signal 27 . This data is in line to what we previously reported in the inner ear, where Smpx was localized exclusively in the HCs of the sensory patches 11 , 17 .
Figure 2 Smpx protein localization in the neuromast mechanosensory hair cells.
…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The Smpx localization in the primary cilium strongly supports the observation that the Smpx-positive cells are the actual mechanosensory HCs responsible for the conversion of mechanical stimuli into electric signal 27 . This data is in line to what we previously reported in the inner ear, where Smpx was localized exclusively in the HCs of the sensory patches 11 , 17 .
Figure 2 Smpx protein localization in the neuromast mechanosensory hair cells.
…”
Section: Resultssupporting
confidence: 93%
“…As we previously demonstrated, the zebrafish Smpx protein inside the inner ear HC was mainly localized at the level of the cuticular plate (CP), an actin-rich structure that is necessary for the correct development of both stereocilia and kinocilia, and to carry out mechanotransduction 17 . Employing a zebrafish model of Smpx deficiency, we showed that the protein exerted a primary function in the proper structural organization of the inner ear HCs sensory bundle as in that both stereocilia and kinocilia displayed evident morphological alterations in terms of number and length 11 , as later also confirmed in a knock-out mouse model 18 . Moreover, we demonstrated that inner ear HCs of Smpx-deficient embryos lack of mechanotransduction activity, providing the first possible explanation for the reported cases of SMPX -linked hearing loss in human patients 4 14 .…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Atp2b2 encodes plasma membrane Ca 2+ ‐ATPase type 2 (PMCA2) that is important for maintaining calcium homeostasis in stereocilia (Street et al, 1998). Other RBM24 targets Grxcr1 , Grxcr2 , Ptprq , and Smpx have also been shown to play important roles in stereocilia development and/or maintenance (Ghilardi et al, 2021; Goodyear et al, 2003; Liu et al, 2018; Odeh et al, 2010; Tu et al, 2021). Therefore, it seems that RBM24 acts downstream of ATOH1 and mainly regulates hair bundle development and function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, smpx , gsdmeb , and otofa are possible target mRNAs of Rbm24a for hair cell morphogenesis and function. Consistently, zebrafish smpx morphants show structural alterations of stereocilia and kinocilia in hair cells as well as impaired hair cell activity [ 49 ].…”
Section: Rbp-mediated Post-transcriptional Regulation In Inner Ear Ha...mentioning
confidence: 93%